Amino acid coating enables micromotor operation in physiological conditions - Jia Sun; Yusen Ding; Yicheng Ye; Fei Wang; Hao Tian; Jiamiao Jiang; Huaan Li; Junbin Gao; Haixin Tan; Fei Peng; Jinyao Tang; Yingfeng Tu (Proceedings of the National Academy of Sciences, 2025)
Physiological environment with high ionic strength will quench the propulsion of micro/nanomotors (MNMs) by suppressing electric double layers, especially for those motors based on electrolyte diffusiophoresis and electrophoresis. Herein, we demonstrate an efficient, general, and simple strategy to improve the ion tolerance of light-driven titanium dioxide (TiO 2 ) micromotors with amino acid surface modification. Compared to the bare TiO 2 counterpart, L-arginine (Arg)-treated TiO 2 micromotors display over 200 times higher ion tolerance, which is mainly attributed to the increased surface conductivity. This simple ion tolerance improvement strategy can also be applicable to other motors driven by self-electrophoresis. As TiO 2 is an efficient sonosensitizer, we combined the light-guiding ability with ultrasound to generate reactive oxygen species to effectively induce in situ tumor apoptosis. We envision that this simple amino acid surface modification can not only provide a solution for MNMs to tolerate the ionic environment but also open up opportunities for further biomedical and translational research of MNMs.